Assessing higher education students’ critical thinking with the PENCRISAL test - Portuguese short version: a psychometric study - Rivas, Silvia F.; Franco, Amanda; Vieira, Rui Marques; Almeida, Leandro S.; Saiz, Carlos (Frontiers in Psychology, 2023)
The development of critical thinking in higher education is fundamental, preparing students to think well, find explanations, make decisions and solve problems. Given the importance of its promotion, its assessment is crucial, since the two are inseparable. Moreover, the number of instruments that are validated to assess critical thinking in the Portuguese language and culture are scarce. We present the validation psychometric study of the PENCRISAL test (short version) to the Portuguese language, a critical thinking assessment test for higher education students, designed and validated in Spain (full and short version), which presents adequate reliability and validity psychometric characteristics to assess key-dimensions of critical thinking. A sample of 225 Portuguese higher education students from three universities (two public and one private) performed a reduced version of the PANCRISAL test. The results obtained allowed replicating the Spanish reduced version in Portugal (only changing one of the six items), and the confirmatory factorial analysis permits to identify two factors intercorrelated, legitimizing the combination of the six items in a global score. This short version can be used as a screening test, and its potential is pointed out to assess students critical thinking to support teaching and research in higher education.